2006
DOI: 10.1002/bit.20752
|View full text |Cite
|
Sign up to set email alerts
|

Control of membrane‐attached biofilms using surfactants

Abstract: The effect of surfactants on membrane-attached biofilms (MABs) was studied in a lab-scale extractive membrane bioreactor (EMB). Twenty-two surfactants were screened for their potential of increasing the cell wall negative charge (i.e. the electrostatic repulsion between bacteria) of Burkholderia sp. JS150 bacterial strain. Surfactants resulting in increased bacterial negative charge were further investigated for their effects on MAB population morphology and MAB attachment behaviour. Microscopic investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…3A and B). Surfactants change flagellar development, leading to altered bacterial attachment and altered biofilm formation (30,60). SPLUNC1 has surfactant activity (21,32), which may play a role in antibiofilm activity.…”
Section: Figmentioning
confidence: 99%
“…3A and B). Surfactants change flagellar development, leading to altered bacterial attachment and altered biofilm formation (30,60). SPLUNC1 has surfactant activity (21,32), which may play a role in antibiofilm activity.…”
Section: Figmentioning
confidence: 99%
“…For example, EPS have been shown to mediate bacterial attachment on membrane filters thereby deteriorating their performance (Frank and Belfort, 2003;Le-Clech et al, 2006;Ridgway and Flemming, 1996;Ridgway et al, 1999). More detailed analysis of EPS components is warranted so that novel membrane biofouling control strategies can be developed and existing ones optimized such as using surfactants, high-shear tangential flow, backwashing, and air scour (Brou et al, 2003;Campbell et al, 1999;Chellam et al, 1998;Cornelissen et al, 2007;Kuberkar et al, 1998;Naja et al, 2006;Rodgers and Sparks, 1992;Splendiani et al, 2006). This study continues our recent investigations of microfiltration (MF) biofouling (Chellam and Xu, 2006;Xu and Chellam, 2005) wherein we present detailed analysis of EPS constituents and further evidence of EPS-induced reduction in backwashing effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have reported that surface preconditioning with biocides has the potential to prevent bacterial adhesion [ 57 , 78 ]. For example, it was shown that biocides can increase the cell wall charge of bacteria and therefore reduce their ability to attach and form biofi lms [ 78 ].…”
Section: Surface Coatingmentioning
confidence: 99%